Outcomes of simultaneous resection for elderly patients with colorectal liver metastasis: A propensity score matching analysis. (24th May 2022) - Chen, Qichen; Zhang, Yizhou; Deng, Yiqiao; Huang, Zhen; Zhao, Hong; Cai, Jianqiang
Abstract: Background: Evidence on simultaneous resection for elderly patients (age ≥ 70 years) with colorectal liver metastasis (CRLM) is lacking. Methods: Four hundred and eighty‐two CRLM patients treated by simultaneous resection were categorised into young group (age < 70 years) and elderly group (age ≥ 70 years). Propensity score matching (PSM1) was performed to adjust for differences in baseline characteristics and compare short‐term outcomes. An additional propensity score matching (PSM2) including short‐term outcomes was performed to analyse survival. Subgroup analysis was performed in patients stratified by the Clinical Risk Score (CRS). Results: After PSM1, 87 young group patients were matched to 50 elderly group patients. Patients in the elderly group had a significantly higher rate of overall post‐operative complications (68.0% vs. 46.0%, p = 0.013). After PSM2, 89 young group patients were matched to 47 elderly group patients. Progression‐free survival (PFS) was comparable between the two groups (median 11.0 months vs. 9.8 months, p = 0.346). Age ≥ 70 independently predicted worse overall survival (OS) (Hazard ratio, HR = 2.57, 95% confidence interval, CI 1.37–4.82) in multivariate analysis. In the subgroup multivariate analysis of patients with CRS score 3–5, age ≥ 70 was independently associated with worse PFS (HR = 1.62, 95% CI 1.01–2.62) and OS (HR = 2.34, 95% CI 1.26–4.35). Conclusions: Simultaneous resection for elderly CRLM patients is acceptable. Further studies are required to determine the optimal treatment for elderly CRLM patients with high CRS scores. Abstract : 482 CRLM patients treated by simultaneous resection were categorized into the young group (age 70 years) and the elderly group (age GreaterEqual;70 years). Although elderly patients receiving simultaneous resection of CRLM have worse OS, similar PFS was reached in the multivariate analysis after propensity score matching. Simultaneous resection for elderly CRLM patients is acceptable.